IWAN SIMATUPANG IN THE WORK: “KERING” - Sianipar, Rosmani (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
This flow departed from the philosophy of Existentialism. Appeared around 1940, existentialism is a tradition of philosophical thought primarily associated with some European philosophers who agree (despite many deep doctrinal differences) that philosophical thought began with human subjects. It is not only human subjects who think, but also human individuals who do, feel, and live. The main value of existentialism is usually thought of as freedom, but in fact the highest value is authenticity. In essence, this philosophy argues that humans are not determined by social factors, biological or heredity, fate and God. Man is determined by himself. Man has free will and he must be responsible for his freedom. Therefore, the human condition is largely determined by what he does.